Development of LKPD Based on Project Based Learning Stoichiometry Material by Utilizing Organic Waste for Phase F SMA/MA - Rahmad, Nafisah Yulia; Suryani, Okta (Universitas Pendidikan Mandalika, 2024)
The project-based learning model is one of the learning models that supports the application of concepts in everyday life. From the results of the questionnaire given, Project Based Learning-based LKPD is needed and it is very important to compile Project Based Learning-based stoichiometry LKPD in supporting learning in the era of an independent curriculum. The type of research used is development research or Educational Design Research (EDR) with the Plomp development model by Tjeerd Plomp. The research was conducted at SMA Negeri 4 Padang with research subjects namely 3 Chemistry Lecturers FMIPA UNP, 2 SMA Negeri 4 Padang teachers and 9 students of class XI SMA Negeri 4 Padang. The object of research is LKPD based on project-based learning on stoichiometry material by utilizing organic waste for phase F SMA / MA. In terms of research, Plomp as a development study has 3 main stages, namely the initial research stage, the prototype formation stage, and the assessment stage. The results showed that all aspects assessed in each component of the validation of project-based learning-based LKPD on stoichiometry material by utilizing organic waste for phase F SMA / MA obtained an average V value of 0.92 with a valid category. The results are very practical for teachers with an average practicality of 91% and practicality for students is very practical with an average practicality of 89%. Based on the results of the study, it was found that the development of LKPD based on project-based learning on stoichiometric material by utilizing organic waste for phase F SMA / MA was developed valid and practical.